Teknologi Switching Digital Dan Non Digital - Agus Gilang Hermawan; Destri Anggraeni; Riga Sahputra Dewa; Didik Aribowo (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In this globalized world, where boundaries are breaking down, effective communication is not just a necessity but a must. It is the lifeblood of every organization, driving its operations and ensuring its growth. However, to achieve this, we need to have a strong system in place. The objectives of this study are to analyze the comparison of the performance of digital and non-digital switching systems, to compare the energy efficiency between digital and non-digital switching technologies in various operational conditions and to determine the simulation of digital and non-digital switching technologies. The method used in this research is a literature review or systematic review by collecting several research journals as reference material.